The First Kansas Band - Edward Bumgardner (Symphony in the Flint Hills, 2011)
In the early records of the Kansas Academy of Science, the name of Joseph Savage occurs frequently. He was the pioneer explorer in the fertile field of Kansas paleontology. As a boy, he lived at Hartford, Vermont, where he was a member of the village brass band. On Sunday, August 26, 1854, he suddenly decided to emigrate to Kansas. This decision would then create the first band in Kansas, finding its home in Lawrence, KS.
Keywords: Kansas; band; Kansas Academy of Science; Joseph Savage; paleontology; Lawrence; Boston; horns; emigrants; Westport Landing; Kansas City; wagons; Shawnee Mission; Delaware; Shawnee; Indians; Native Americans; cornet; clarinet; free-state; Kansas Conference of the Methodist Church; Gov. Charles Robinson; Quantrill; Quantrill& #x27; s Raid; KU; Bismark Grove; settlers; musical instruments